Facilities and maintenance audit of petrol station / Norfarhana Nordin - Nordin, Norfarhana (Faculty of Architecture, Planning and Surveying, 2008)
Introduction on the petrol station and the historical background of it are discussed in detail. The risk management of the petrol stations is defined and listed. The problem and issue stated and the objectives of the dissertation are explained. The scope of the study which were conducted in Klang Valley area were made clear and the understanding of the methodology used are stated in plain.